Bibliometric analysis of nurses’ moral distress research - Li, Xin; Liu, Xiao; Wang, Fengxia; Zhang, Yi; Huang, Jianxin; Wang, Jihong; Zhou, Xiaohuan (Frontiers in Psychiatry, 2024)
ObjectiveTo identify the research status of nurses’ moral distress and predict emerging research hotspots and development trends.MethodsArticles on nurses’ moral distress were retrieved from the Web of Science Core Collection database from the inception of the database to 2024. A bibliometric analysis was conducted using VOSviewer and CiteSpace software to analyze publication distributions by country, institution, journal, author contributions, keyword trends, and reference co-citations.ResultsOur study analyzed 1,781 documents, revealing a notable increase in publications after 2017, with contributions from 88 countries and 2,301 institutions worldwide. The United States and China were prominent contributors, highlighting global interest in this area. Analyses of keywords and cited references reveal emerging research topics such as “COVID-19”, “burnout”, and “moral resilience”.ConclusionThis bibliometric review sheds light on the growing academic interest in nurses’ moral distress, emphasizing key themes and outlining future research directions. By charting the development of this domain, our study provides critical insights, guiding the investigation of complex ethical issues in nursing and enhancing understanding of nurses’ moral distress.